Cretophengodidae, a new Cretaceous beetle family, sheds light on the evolution of bioluminescence - Li, Yan-Da; Kundrata, Robin; Tihelka, Erik; Liu, Zhenhua; Huang, Diying; Cai, Chenyang (Proceedings. Biological sciences, 2021)
Bioluminescent beetles of the superfamily Elateroidea (fireflies, fire beetles, glow-worms) are the most speciose group of terrestrial light-producing animals. The evolution of bioluminescence in elateroids is associated with unusual morphological modifications, such as soft-bodiedness and neoteny, but the fragmentary nature of the fossil record discloses little about the origin of these adaptations. We report the discovery of a new bioluminescent elateroid beetle family from the mid-Cretaceous of northern Myanmar (ca 99 Ma), Cretophengodidae fam. nov. Cretophengodes azari gen. et sp. nov. belongs to the bioluminescent lampyroid clade, and would appear to represent a transitional fossil linking the soft-bodied Phengodidae + Rhagophthalmidae clade and hard-bodied elateroids. The fossil male possesses a light organ on the abdomen which presumably served a defensive function, documenting a Cretaceous radiation of bioluminescent beetles coinciding with the diversification of major insectivore groups such as frogs and stem-group birds. The discovery adds a key branch to the elateroid tree of life and sheds light on the evolution of soft-bodiedness and the historical biogeography of elateroid beetles.
Keywords: světluškovití; fossil; zkameněliny; brouci; Fireflies; Cretaceous Terrestrial Revolution; Animals; Elateroidea; mužské pohlaví; Male; Phylogeny; biogeography; zvířata; fylogeneze; Myanmar; bioluminescence; Coleoptera; Fossils